Developing a Charter of Physical Activity and Sport for Children and Youth - Robert J. Parker; Elizabeth J. Elliott; Adeli Georga; Michael Booth (Elsevier, 2003)
Abstract Objectives: The purpose of this project was to develop a Charter of Physical Activity and Sport for Children and Youth. Its primary purpose is to provide a philosophical framework to support participation, enjoyment and safety in physical activity and sport for all Australian children and youth. Methods: The development of the charter was initiated by The Children's Hospital at Westmead, New South Wales (NSW) and was developed in consultation with 60 parent and community groups, sporting and recreational clubs and organisations, professional associations, schools, local and state government organisations and national sporting bodies. Results: The charter emphasises that physical activity and sport should be a fundamental right of all children and youth; be enjoyable; enhance health and well‐being; be available for children and youth with disabilities and chronic illness; include those who are geographically isolated; be safe and free from physical and psychological abuse; be free from exploitation for political, commercial or financial gain; avoid elitism; and be encouraged by a wide cross section of the community. Conclusions: Broad consensus has been reached by most organisations with a role or interest in child and youth sport and physical activity on the foundations for participation in these activities by young people living in NSW. Implications: Research and evaluation of practice in Australia is essential and will allow development of evidence‐based guidelines for participation in physical activity and sport for young Australians, based on the philosophy of the charter.